A STUDY ON KNOWLEDGE AND PRACTICES OF ANTENATAL CARE AMONG PREGNANT WOMEN IN RURAL AREAS OF BARABANKI DISTRICT - Shwetambari Srivastava; Raj Shekhar Tiwari; Dr. Zainab Khan (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background Appropriate antenatal care (ANC) is one of the pillars of this initiative. Antenatal care is considered asa backbone of obstetrical services of any health of pregnant women and is the way in which maternal and fetal complications are detected and managed. It highlights the care of antenatal mothers as an important element in maternal healthcare as appropriate care will lead to successful pregnancy outcome and healthy babies. Safe motherhood by providing good antenatal care (ANC) is very important to reduce maternal mortality ratio and infant mortality rate and to achieve millennium development goals.ObjectiveThe objective of the present study is awareness about the ANC among pregnant women, knowledgeand practices regarding elements of ANC care and to give suggestions to improve the maternal health practices.Study AreaBarabank district catchment area of RHTCStudy populationAll pregnant women registered at RHTC HIMS Barabanki.ResultsThe study shows that ANC women, 32.5 % are illiterate so they are not aware about their health during their pregnancy and health workers don’t provide them adequate information about the Government schemes. Maximum number of pregnant women are aware of their health and fetus, visit health centers regularly for their ANC checkups. They agreed that smoking and alcohol consumption is bad for fetus as it causes growth retardation. Some of thepregnant women agreed for the IFA tablet supplementation during pregnancy instead of that they are not taking IFA tablets during their pregnancy. Some of the respondents delivered their baby at home because of their fear of miscarriage or risk at hospital. Pregnant women having knowledge about ANC was found to be statistically significant who are literate. Practices were found to be statistically significant in pregnant women attending regular ANC visits.